Legal socialization and subcultural norms: Examining linkages between perceptions of procedural justice, legal cynicism, and the code of the street. (March 2019) - Moule, Richard K.; Burruss, George W.; Gifford, Faith E.; Parry, Megan M.; Fox, Bryanna
Abstract: Purpose: The procedural justice model of legal socialization holds that perceptions of unfair treatment by legal authorities foster cynicism toward the law. Subcultural theories argue negative perceptions of those same authorities, and resulting cynicism toward the law, also foster belief in antisocial norms. The current study considers the overlap of these literatures by exploring the psychometric properties of the core constructs found in both models and the relationships between these constructs. Methods: Using a national sample of 702 American adults, confirmatory factor analysis and structural equation modeling are used to assess the relationships between perceptions of procedural justice, legal cynicism, and the code of the street. Results: Confirmatory factor analysis indicates legal cynicism and the street code are empirically distinct, but moderately correlated. Structural equation modeling shows that perceptions of procedural justice and legal cynicism are both significantly associated with street code beliefs. Perceptions of procedural justice also have a significant indirect effect on street code beliefs through legal cynicism. Alternative model specifications demonstrate a persisting association between cynicism and the street code, but mixed evidence for relationships between experiences with police and belief in the code. Conclusions: Findings highlight opportunities to better integrate the legal socialization and subcultural literatures. Highlights: Theories of legal socialization and subcultural norms have developed independently over the past two decades Measures of legal cynicism and the code of the street are found to be empirically distinct, but are moderately correlated Perceptions of procedural justice exert direct and indirect effects on individual belief in the code of the street Findings highlight opportunities to better understand the overlap and intersection of these literatures